BUSINESS TRENDS OF HALAL AND THOYYIB FOOD DURING THE PANDEMIC: A REVIEW FROM ISLAMIC ECONOMICS IN PONGGOK AND JANTI TOURISM DESTINATIONS - Fredi Setyono (Journal of Management and Islamic Finance, 2021)
The purpose of this study is to explore the trends of the halal food business as well as the problems they encounter at hard times and whether they can survive in the current conditions. This study used qualitative research methods through interviews with several food sellers in Ponggok and Janti tourism destinations. The study shows that sellers at Ponggok and Janti, Klaten have been running a halal food business for Islamic economic review. In running their business, sellers sell halal food, not gharar and maysir. However, there are still sellers who did not use the financing and services of the Islamic financial institutions to run their business, some are still using conventional banks to run their business. Hence, it is very difficult for them to have halal certification. During the Covid-19 pandemic, sellers have dropped their sales turnovers resulting in no profit.